1996
DOI: 10.7182/prtr.1.6.2.n2pl238265177gpm
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life outcomes associated with variable posttransplant prednisone dosing regimens

Abstract: Prednisone tapering has become more common in the management of transplant recipients. Benefits of this practice, however, must be weighed against the risks. This study identified outcomes associated with variable low dose prednisone protocols. The study sample included 98 kidney and kidney-pancreas transplant recipients 1 year after transplant. Graft function, side effects of steroid therapy, and quality of life were recorded on patients receiving 0 (n = 5), 1 to 5 (n = 4), 5 to 7.5 (n = 5), 7.5 to 10 (n = 21… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Although statistically significant differences are important to note, Riley et al (20,21) reported that a score differential of 3 points (0.6 SD) is correlated with meaningful clinical differences. Using this more stringent criteria, CKD patients' functional health is comparable to that of their peers except in the area of physical activity, where they report being less physically active than control group adolescents.…”
Section: Comparison Of Health Status Of Adolescents With Ckd and Adolmentioning
confidence: 99%
“…Although statistically significant differences are important to note, Riley et al (20,21) reported that a score differential of 3 points (0.6 SD) is correlated with meaningful clinical differences. Using this more stringent criteria, CKD patients' functional health is comparable to that of their peers except in the area of physical activity, where they report being less physically active than control group adolescents.…”
Section: Comparison Of Health Status Of Adolescents With Ckd and Adolmentioning
confidence: 99%
“…Her doctoral studies laid the foundation for quality-of-life studies and social network mapping. Her many papers [2][3][4][5] reflect this work with colleagues and mentors at the University of Tennessee.…”
Section: A Pacesetter For Advanced Practicementioning
confidence: 99%
“…The concept represents individual responses to the physical, mental, and social effects of illness on daily living, which influence the extent to which personal satisfaction with the circumstances of life can be achieved (Lukkarinen & Hentinen, 1998). QoL is also a result of a patient's perceptions, and the unique experiences of life, and the cultural, ethnic, and religious values of an individual determine how it is judged (Hathaway et al. , 1996).…”
Section: Hrqolmentioning
confidence: 99%